Senescence-induced p21high macrophages contributed to CD8+ T cells-related immune hyporesponsiveness in kidney transplantation via Zfp36/IL-27 axis - Tingting Zhu; Qixia Shen; Lingling Shen; Yucheng Wang; Bochen Zhu; Lifeng Ma; Shi Feng; Cuili Wang; Sijing Yan; Jingyi Li; Zhimin Chen; Jingyi Zhou; et al. (Cell Discovery)
Abstract Recipients’ age has emerged as a key factor that impacts on acute renal allograft rejection and graft survival. Age-related functional and structural changes in the immune system have been observed, yet the precise influence of aged immunity on kidney transplant remains unclear. In an initial retrospective analysis of clinical data gathered from two major centers in China and Germany, we found a correlation between aging and mitigated rejection outcomes in kidney recipients. To study the mechanism, we performed kidney transplantation on mice and observed attenuated allograft rejection in senescent recipients. Single-cell transcriptome analysis of allograft kidneys indicated a protective role of p21high macrophages in aged mice. Supernatant collected from p21high macrophage primary culture inhibited the cytotoxic function and proliferation of CD8+ T cells. Zfp36 is highly expressed in senescent p21high macrophages. To determine its role in renal allograft rejection, we studied mice with Zfp36 conditionally deleted in macrophages (Zfp36-cKO). These mice developed exacerbated allograft rejection with enhanced IL-27 production and CD8+ T cell hyperactivation. Inhibition of IL-27 with neutralizing antibody or deletion of IL-27 receptor on CD8+ T cells reversed acute renal allograft rejection in Zfp36-cKO mice. Moreover, in vitro silencing Zfp36 with siRNA led to impaired degradation of IL-27 p28 mRNA and a subsequent increase of IL-27 in p21high macrophages. In conclusion, senescent macrophages protect renal allograft rejection by suppressing CD8+ T cells via a Zfp36/IL-27-dependent mechanism. These findings may provide innovative therapeutic strategies for addressing kidney allograft rejection.